Perspektif Hukum terhadap Status Anak Luar Nikah Dalam Memperoleh Hak Waris Kompilasi Hukum Islam - Yapiter Marpi (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2019)
This study aims to determine and discuss the perspective of inheritance law on the status of out-of-wedlock children in obtaining the inheritance rights of Islamic law compilation. The method used is a qualitative method using secondary data and primary data for completeness of data, data analysis used using normative analysis. Based on the results of research, among others, first, the position of out-of-wedlock children according to Islamic Law is based on nasab as the legality of family relations based on blood relations, as a result of legal marriage. The problem is that there is no relationship between the child's relationship with his biological father; there are no rights and obligations between the child and his biological father, inheritance and so on; if by chance the child is a woman, then the biological father cannot be the guardian, so that the guardian can be a child out of wedlock; secondly, the status of inheritance rights for out-of-wedlock children according to Islamic law only have a mutual inheritance relationship with the family from the mother's side, however there is a need for legal breakthroughs related to this, namely in the Islamic inheritance system, there are grant institutions in the form of giving biological father's day and can also the wills of the Mandatory from his biological father. Keywords; Inheritance rights, out-of-wedlock children, compilation of islamic law.